Nurse Knowledge Sharing Portal - Salleh, Nor Safwan Amirul (Universiti teknologi petronas, 2008)
This study will be focusing on the Nurse Knowledge Sharing Portal. The purpose of this project is to use Knowledge Management in order to have good information sharing system among the medical staff. The project will be based on Knowledge management and web based development. By doing so, it will support and improve distributed information sharing among hospital staff especially nurses. Nurses can easily find the information of technique, procedure and way how to deal with disease by using this system it implement this project, and Joomla is used as the e-learntngmodel. Besides, the information about new disease technique, procedure and way how to deal with it is provided in this system and will represent in informational data. The scope of study of this proposed project is within nurses' community itself. The target users of course are among nurses as the designed of this sharing system will be within hospital local area network. To gather information for this project 1have do some research according to the problem that faced by medical staff. These are some methods, which I use to gather the information such as survey form, journal, health magazine, and also internet. Methodology to be used in executingthis project will be incremental and prototyping life cycle model where the development of the site will be based on prototype of component or module per module. To accomplish this project I will develop an online sharing work space like blogs, and forum. Information Sharing System will help medical staff especially nurses to efficiently do their job while doing it safely.